A baculovirus-mediated strategy for full-length plant virus coat protein expression and purification - Araújo, Daniel Mendes Pereira Ardisson de (2013)
Background: Garlic production is severely affected by virus infection, causing a decrease in productivity and quality. There are no virus-free cultivars and garlic-infecting viruses are difficult to purify, which make specific antibody production very laborious. Since high quality antisera against plant viruses are important tools for serological detection, we have developed a method to express and purify full-length plant virus coat proteins using baculovirus expression system and insects as bioreactors. Results: In this work, we have fused the full-length coat protein (cp) gene from the Garlic Mite-borne Filamentous Virus (GarMbFV) to the 3′-end of the Polyhedrin (polh) gene of the baculovirus Autographa californica multiple nucleopolyhedrovirus (AcMNPV). The recombinant baculovirus was amplified in insect cell culture and the virus was used to infect Spodoptera frugiperda larvae. Thus, the recombinant fused protein was easily purified from insect cadavers using sucrose gradient centrifugation and analyzed by Western Blotting. Interestingly, amorphous crystals were produced in the cytoplasm of cells infected with the recombinant virus containing the chimeric-protein gene but not in cells infected with the wild type and recombinant virus containing the hexa histidine tagged Polh. Moreover, the chimeric protein was used to immunize rats and generate antibodies against the target protein. The antiserum produced was able to detect plants infected with GarMbFV, which had been initially confirmed by RT-PCR. Conclusions: The expression of a plant virus full-length coat protein fused to the baculovirus Polyhedrin in recombinant baculovirus-infected insects was shown to produce high amounts of the recombinant protein which was easily purified and efficiently used to generate specific antibodies. Therefore, this strategy can potentially be used for the development of plant virus diagnostic kits for those viruses that are difficult to purify, are present in low titers or are present in mix infection in their plant hosts.